Poka-Yoke in Problem Based Learning for Engineering Students to Increase Employability Rate: A Preliminary Study - Murugan Subramaniam , Nishantini Loganathan , Muhammad Khair Noordin (International Journal of Advanced Science and Technology, 2020)
Cost down and profit making are the industry's ultimate goal. In this sense, product qualityand customer satisfaction must be complied with in order to create a continuous companyconnection between clients. Product quality and customer satisfaction are heavily linked toproblem solving skills. The greater the problem-solving skills; the stronger from the client pointof perspective is the reputation of employers. That's why the statistics show that problem-solvingabilities become one of the most significant skills employers search for from engineers (Outlooket al., 2019). A minor mistake in the manufacturing system will jeopardize the entiremanufacturing operations; resulting in unnecessary waste in terms of price and time. Therefore,it’s equally essential for new graduates to be fitted with problem-solving abilities instead oftechnical abilities alone to penetrate into the job market. The goal of this study is to createengineering students with problem-solving abilities through Poka-Yoke or Mistake ProofMethodology. The aim of this article is to evaluate current literature on problem-solving skillsfor graduate engineers through a systematic literature review through Poka-Yoke Methodology.This document analyzes literature primarily from Scopus and Web of Science through electronicdatabases. This document summarizes the methodology hired by Poka-Yoke in the engineeringsector as of now. Based on this, engineers can distinguish and comprehend the strategy ofproblem-solving abilities in the manufacturing atmosphere to avoid early-stage processproblems or errors and boost productivity.